Alternative Oxidase (AOX) Senses Stress Levels to Coordinate Auxin-Induced Reprogramming From Seed Germination to Somatic Embryogenesis—A Role Relevant for Seed Vigor Prediction and Plant Robustness - Mohanapriya, Gunasekaran; Bharadwaj, Revuru; Noceda, Carlos; Costa, José Hélio; Kumar, Sarma Rajeev; Sathishkumar, Ramalingam; Thiers, Karine Leitão Lima; Santos Macedo, Elisete; Silva, Sofia; Annicchiarico, Paolo; Groot, Steven P.C.; Kodde, Jan; et al. (Frontiers in Plant Science, 2019)
Somatic embryogenesis (SE) is the most striking and prominent example of plant plasticity upon severe stress. Inducing immature carrot seeds perform SE as substitute to germination by auxin treatment, can be seen as switch between stress-levels associated to morpho-physiological plasticity. This experimental system is highly powerful to explore stress response factors that mediate the metabolic switch between cell and tissue identities. Developmental plasticity per se is an emerging trait for in vitro-systems and crop improvement. It is supposed to underlie multi-stress tolerance. High plasticity can protect plants throughout life cycles against variable abiotic and biotic conditions. We provide proof-of-concepts for the existing hypothesis that AOX can be relevant for developmental plasticity and be associated to yield stability. Our perspective on AOX as relevant coordinator of cell reprogramming is supported by real-time PCR analyses and gross metabolism data from calorespirometry complemented by SHAM-inhibitor studies on primed, ‘elevated partial pressure of oxygen (EPPO)’-stressed, and endophyte-treated seeds. In silico studies on public experimental data from diverse species strengthen generality of our insights. Finally we highlight ready-to-use concepts for plant selection and optimizing in vivo and in vitro propagation that do not require further details on molecular physiology and metabolism. This is demonstrated by applying our R&T concepts to pea genotypes with differential yield performance in multi-location fields and chickpea types known for differential robustness in field. By using these concepts and tools appropriately, also other marker candidates than Alternative Oxidase (AOX) and complex genomics data can be efficiently validated for pre-breeding and